2019
DOI: 10.1029/2018jb017130
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Observations of the Prompt Elastogravity Signals Heralding Direct Seismic Waves

Abstract: The recent first observations of the prompt elastogravity signals (PEGS) induced by the 2011 Mw = 9.1 Tohoku megathrust earthquake generated interest in how these signals might best be observed, especially for lower‐magnitude events. Simulations of these signals preceding the direct P wave, for different depths and focal mechanisms, first reveal that shallow strike‐slip earthquakes offer a better detection potential than subduction megathrust earthquakes. Consistently, clear PEGS are observed at several broadb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 39 publications
(76 reference statements)
0
23
0
Order By: Relevance
“…Previous studies have found that early P wave arrivals carry information about the overall earthquake size (Iio, 1995;Beroza & Ellsworth, 1996;Allen & Kanamori, 2003;Olson & Allen, 2005), but such correlations bear large uncertainties that necessitate additional information, such as attenuation parameters, in order to conduct meaningful early magnitude estimation (Wu et al, 2006;Colombelli et al, 2014;Noda & Ellsworth, 2016). The direct P wave arrival, however, represents only a small fraction of the available and potentially deterministic information (Vallée et al, 2017;Vallée & Juhel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that early P wave arrivals carry information about the overall earthquake size (Iio, 1995;Beroza & Ellsworth, 1996;Allen & Kanamori, 2003;Olson & Allen, 2005), but such correlations bear large uncertainties that necessitate additional information, such as attenuation parameters, in order to conduct meaningful early magnitude estimation (Wu et al, 2006;Colombelli et al, 2014;Noda & Ellsworth, 2016). The direct P wave arrival, however, represents only a small fraction of the available and potentially deterministic information (Vallée et al, 2017;Vallée & Juhel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in the research on PEGS has yielded new advances that go far beyond the K19 study. Readers interested in how PEGS can be optimally observed may refer to the more sophisticated stacking approaches described by Montagner et al (2016) and Vallée and Juhel (2019). Vallée and Juhel (2019) also show how multiple PEGS observations made for earthquakes of different focal mechanisms and depths are accurately modeled by the methods described by V17 and Juhel et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Readers interested in how PEGS can be optimally observed may refer to the more sophisticated stacking approaches described by Montagner et al (2016) and Vallée and Juhel (2019). Vallée and Juhel (2019) also show how multiple PEGS observations made for earthquakes of different focal mechanisms and depths are accurately modeled by the methods described by V17 and Juhel et al (2019). Therefore, the remaining challenges today are no longer to show that PEGS are well understood, modeled, and observed for magnitudes larger than 8, but to lower this magnitude threshold and to reduce the detection delay, in order to make PEGS even more valuable for early warning systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the quantitative use of prompt gravity signals in the future, these forward models await validation using authorized data that has reduced uncertainty. For the reduction of uncertainty in data, the use of stacked traces of observed waveforms will be useful [5,6,24]( §3). Range Seismograph Network of Japan (F-net) [3].…”
Section: (C) Spherical Earth Model Considering Fully Coupled Elasto-gmentioning
confidence: 99%